Zilola INNOVATIVE APPROACH TO TEACHING FOREIGN LANGUAGES IN PRESCHOOL EDUCATION INSTITUTIONS: INNOVATIVE APPROACH TO TEACHING FOREIGN LANGUAGES IN PRESCHOOL EDUCATION INSTITUTIONS - Doniyeva, Zilola (Журнал иностранных языков и лингвистики, 2022)
Teaching foreign languages, especially English, in Preschool Educational Institutions associated with the creation of an innovative theory of education. This is education system technology, pedagogical technologies to the education system reforming the education system by adding education effectiveness increase; ensure the socialization of the individual, specific in this regard foreign education to the child in the educational process to achieve success the reason for forming a relationship by absorbing their achievements will be.